2014
DOI: 10.2355/isijinternational.54.620
|View full text |Cite
|
Sign up to set email alerts
|

Development of Pellet-Sinter Composite Agglomerate for Blast Furnace

Abstract: Microfines of iron ore are generally utilized in Blast furnace in form of indurated pellets because sinter bed has limitation of accepting fines. Charging of acid pellets with basic sinter is the normal practice in blast furnace. However induration of pellets is very cost intensive. Further more, due to low angle of repose pellets distribution during charging with other materials in blast furnace creates inhomogeneous distribution. In order to alleviate the above problem, a composite mass of acid pellet and ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…Since mill scale is a source of magnetite in a pellet, it may improve the strength of pellet. Pal et al [14] used mill scale as in-situ heat source in their Pellet-Sinter Composite Agglomerates (P-SCA) and found a good strength improvement. Rajshekar et al [15] found a better sintering property by using mill scale in hematite ore than by using pure hematite ore.…”
Section: Introductionmentioning
confidence: 99%
“…Since mill scale is a source of magnetite in a pellet, it may improve the strength of pellet. Pal et al [14] used mill scale as in-situ heat source in their Pellet-Sinter Composite Agglomerates (P-SCA) and found a good strength improvement. Rajshekar et al [15] found a better sintering property by using mill scale in hematite ore than by using pure hematite ore.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, highly fluxed pellet reduces the basic sinter acceptance capacity of blast furnace. Acidic hematite pellet is advantageous because blast furnace can accept more basic sinter and replace lump ore charging Pal et al 2014aPal et al , 2014b Magnetite is an inverse spinel structure with the oxygen ions forming an ABCABC layered packing. The Fe 2+ occupies the octahedral sites in between the oxygen atoms and Fe 3+ occupies both tetrahedral and octahedral sites.…”
Section: Introductionmentioning
confidence: 99%
“…However, use of mill scale in pellet is also an important aspect. Pal et al (2014b) used mill scale as in situ heat source in their Pellet-Sinter Composite Agglomerates (PSCA) and found good strength improvement. Ahmed et al (1997) observed low drop numbers in complete mill scale pellets which was increased with the addition of lime as binder.…”
Section: Introductionmentioning
confidence: 99%
“…It is worthy to be mentioned, the investigators 28) comment that some separate pellets in agglomeration product and the strength of those pellets is the key factor of sinter quality. In fact, their understanding is inaccurate for blinding to the pelletized feed is embedded into the matrix part in CAP product.…”
Section: Mineralization Characterization Of Titanomagne-mentioning
confidence: 99%
“…Consequently, it is proved that CAP is an effective and efficient for titanomagnetite concentrate agglomeration, in terms of productivity, energy consumption and CO 2 emission. 28) b) Agglomeration Products Properties Table 7 shows the main properties of products from CAP and TSP. The tumbler index increases by 13.08%.…”
Section: Comparison Between Cap and Tspmentioning
confidence: 99%